Current relation between ecological footprint and country risk premium - Boutin, Landry François Baptiste (2020)
In a context of yearly ecological overshoot, policies and financial initiatives for a sustainable management of natural resources appear in increasing number. This dissertation aims to illustrate the current trends of foreign investments with regard for nature conservation by examining the potential relation between ecological footprint per capita (from the Global Footprint Network database) and country risk premium (as published yearly by Aswath Damodaran). The analysis is conducted on a panel of 91 countries (43 developed countries and 48 emerging countries) across 17 years (from 2000 to 2016), using panel data analysis methods such as pooled regression, fixed effect and random effect models. The findings show a significant correlation between the variables, with more intensity for developed countries. The best goodness-of-fit is found using a “random” model for times effects, with the inverse of ecological footprint values as explanatory variables. Therefore the results suggest that the relation between ecological footprint and country risk premium follows an inverse trend, meaning that countries with a very low ecological footprint tend to have unusually high risk premia, and that risk premia tend to get closer to 0% when the ecological footprint is high. The results can be interpreted as a complementarity relation rather than a cause to effect relation, meaning that increased attractiveness to foreign investors by the mean of low country risk premium currently implies a higher consumption of biocapacity.